PERHITUNGAN DAN ANALISIS LOSSES, DIAMETER EFEKTIF ROTOR, DAN PENYERAPAN DAYA DAN ENERGI PADA DIFFUSER AUGMENTED WIND TURBINE (DAWT) - Atmadi, Sulistyo; Fitroh, Ahmad Jamaludin (BRIN Publishing, 2011)
The use of diffuser in wind turbine (DAWT) is aimed at increasing the effective speed to produce a higher power. A bigger and heavier turbine results in difficulty in manufacturing the turbine orientation system. This research consists of three parts i.e. the calculation and analysis of the losses, determination of the effective diameter of the rotor, and the calculation and analysis of the absorbed energy by DAWT. The losses calculation and analysis is based on the friction between the airflow and wall. The diameter of the rotor is choosen in the diffuser area which has minimum turbulence flow produced by the wind angle. The calculation and analysis of the power is based on its rotor diameter. Then the power converted to become energy. In this research, DAWT is assumed to have no orientation system so that easily manufactured, i.e. the rotor is oriented at a single direction. Wind direction and frequency is selected in three configurations. In the first configuration, the wind direction comes from all the twelve wind source direction with the same frequency in the 24 hour period, producing 2 hourly periods for every wind direction. In the second configuration, wind from 90° and 270° or perpendicular to the axial turbine axes are eliminated, and hence producing 10 different wind directions at 2.4 hourly periods. In the third configuration, the turbine is set at the beach whereby the wind direction comes only at two direction; the sea and land wind directions. At these conditions, the wind is assumed to come at 0°, 30°, 150°, 180°, 210°, and 330°. The aim of this research is to calculate the energy absorption of the wind rotor, and comparing with those produced without the diffuser system in place. In this research, a 2m rotor diameter and 4m diffuser diameter is selected, power coefficient of 0.3, wind speed of 5m/sec, and these parameters are constant for the 24 period under analysis. The result of the calculation shows that there are losses near wall especially for high wind angle. The rotor diameter have chossen about 1,940 m. The energy absorption of the wind rotor without the diffuser is 6.231 kJ. The energy absorption values for the 1st, 2nd and 3rd configuration with the diffuser produce 54.361, 65.234, and 101.316 kJ respectively. It shows that the use of diffuser in the wind rotor could produce an increase of up to 9 to 16 times in the power absorption of the rotor.